Penerapan Metode Waterfall Dalam Sistem Informasi Pembuatan Surat Rekomendasi BPJS Kelas III - Aria, Ririn Restu; Rosdiana, Annisa Nur (STIKOM Tunas Bangsa Pematangsiantar, 2019)
BPJS health is a social security organizer that organizes health insurance for the community. One of the most important activities is the preparation of a BPJS recommendation letter for class three which is managed by the Bogor City Social Service. To make a recommendation letter, the applicant must submit the letter to the service department and must be approved in advance by the head of the social service office. so that letter-writing services can run quickly and effectively, applications must be made available that make it easy for the head of the office to see and approve the existing application letter. In this study the method used is the waterfall so that it can understand the overall problem and produce applications that suit the needs of users. The purpose of this study is to provide convenience for the applicant, the service department and the head of the office in the process of submitting a BPJS recommendation letter and approval made in the proposed recommendation letter.